Optically induced change of photoelectric properties of CdMnTe crystals - Savkina, R.K.; Sizov, F.F.; Smirnov, A.B. (Functional Materials, 2005)
To study the optically induced transformation of the point defect system under strong ans weak excitation from the intrinsic absorption hv > Eg, photoelectric and electric properties of semiconductor solid solutions С₁-хМnхТе (x = 0.08 + 0.1) have been studied at 78 and 300 K. It has been found that the weak optical excitation (hv - 2 eV) under simultaneous fast chilling down to 78 К results in a dramatic drop of the photocurrent and increase of the crystal dark resistance by more than a decimal order. The crystal photosensitivity is recovered in part by ultrasonic annealing or after a prolonged exposure at room temperature. A possible mechanism of that effect is discussed associated with the photoinduced ionization of manganese ions. The pulse laser irradiation ( λ = 694 nm, τl = 20 ns) at an under-threshold power results in photosensitization of the Cd₁-хMnxTe crystals not only in the irradiation zone but also in the control region.